Immune Monitoring of Patients With Primary Immune Regulation Disorders Unravels Higher Frequencies of Follicular T Cells With Different Profiles That Associate With Alterations in B Cell Subsets - Caldirola, María Soledad; Martínez, María Paula; Bezrodnik, Liliana; Zwirner, Norberto Walter; Gaillard, María Isabel (Frontiers in Immunology, 2020)
Primary immune regulation disorders lead to autoimmunity, allergy and inflammatory conditions due to defects in the immune homeostasis affecting different T, B and NK cell subsets. In this work, we analyzed the T and B cell compartments of 15 PID patients with dysregulation, including 3 patients with STAT1 GOF mutation, 7 patients with CVID with dysregulation, 3 patients with mutations in CTLA4, 1 patient with CD25 mutation and 1 patient with STAT5b mutation, and compared them with healthy donors and CVID patients without dysregulation. CD4+ and CD8+ T cells from the patients exhibited a significant decreased frequency of naïve and regulatory T cells with increased frequencies of activated cells, central memory CD4+ T cells, effector memory CD8+ T cells and terminal effector CD8+ T cells. Patients also exhibited a significantly increased frequency of circulating CD4+ follicular helper T cells, with altered frequencies of cTfh cell subsets. Such cTfh cells were skew towards cTfh1 cells in STAT1 GOF, CTLA4 and CVID patients, while the STAT5b deficient patient presented a skew towards cTfh17 cells. These alterations confirmed the existence of an imbalance in the cTfh1/cTfh17 ratio in these diseases. In addition, we unraveled a marked dysregulation in the B cell compartment, characterized by a prevalence of transitional and naïve B cells in STAT1 GOF and CVID patients, and of switched-memory B cells and plasmablast cells in the STAT5b def patient. Moreover, we observed a significant positive correlation between the frequencies cTfh17 cells, switched-memory B cells and serum IgG. Therefore, primary immunodeficiencies with dysregulation are characterized by a skew towards an activated/memory phenotype within the CD4+ and CD8+ T cell compartment, accompanied by abnormal frequencies of Tregs, cTfh and their cTfh1 and cTfh17 subsets that likely impact on antibody production, which likely contributes to their autoimmune and inflammatory conditions. Therefore, assessment of these alterations by flow cytometry constitutes a simple and straightforward manner to improve diagnosis of these complex clinical entities that may impact early diagnosis and patients’ treatment. Also, our findings unravel phenotypic alterations that might be associated, at least in part, with some of the clinical manifestations observed in these patients.